2020
DOI: 10.1111/hae.14030
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy interventions for pain management in haemophilia: A systematic review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Many reviews searched for current evidence of the effectiveness of physiotherapy interventions on musculoskeletal pain and function. [ 3 , 6 , 7 , 15 ] All authors agree on the multidisciplinary approach to patients with hemophylia, confirming the need for physiotherapy and its safety with respect to bleeding related to exercise, [ 7 ] but unclear conclusions are available with respect to the best intervention to recommend. [ 3 ] Most of the authors reported benefits by physiotherapy programs based on the recovery of flexibility, strength, balance, proprioception, and aerobic capacity both through land-based and aquatic exercise [ 8 , 10 , 14 , 16 ] as well by physical modalities (transcutaneous electrical nerve stimulation laser, ultrasounds, neuromuscular electrical stimulation, electromagnetic fields, and kinesiotaping) [ 5 , 17 , 18 ] and joint mobilizations.…”
Section: Discussionmentioning
confidence: 99%
“…Many reviews searched for current evidence of the effectiveness of physiotherapy interventions on musculoskeletal pain and function. [ 3 , 6 , 7 , 15 ] All authors agree on the multidisciplinary approach to patients with hemophylia, confirming the need for physiotherapy and its safety with respect to bleeding related to exercise, [ 7 ] but unclear conclusions are available with respect to the best intervention to recommend. [ 3 ] Most of the authors reported benefits by physiotherapy programs based on the recovery of flexibility, strength, balance, proprioception, and aerobic capacity both through land-based and aquatic exercise [ 8 , 10 , 14 , 16 ] as well by physical modalities (transcutaneous electrical nerve stimulation laser, ultrasounds, neuromuscular electrical stimulation, electromagnetic fields, and kinesiotaping) [ 5 , 17 , 18 ] and joint mobilizations.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, the studies included in the meta‐analysis published in 2007 about the efficacy of psychological interventions in patients with arthritis underline the improvement in QoL achieved by CBT programmes for CP management 34,35 . Likewise, physiotherapy programmes to improve CP in chronic knee pain also obtained improvements in QoL 36 although a recent review states that there is no clear effect of physiotherapy in improving QoL in PwH 37 …”
Section: Discussionmentioning
confidence: 96%
“…After a bleed, the method “Protection, Optimal load, Ice, Compression, Elevation” (POLICE) is recommended first followed by the progressive reestablishment of muscle strength, starting with isometric exercises, concentric isotonic exercises, eccentric isotonic exercises, open kinetic chain and finally closed kinetic chain [ 8 , 9 , 10 , 11 ]. Manual therapy and exercise can be complemented with NMES, TENS, ultrasound, hydrotherapy, and gait reeducation, in addition to the use of therapeutic education to improve the quality of life and the perception of pain in these patients [ 12 , 13 , 14 ]. Moreover, chronic pain appears in 35–50% of people with hemophilia, with 40% of these patients indicating that health professionals do not treat their pain well, requiring a better approach from a biopsychosocial sphere [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manual therapy and exercise can be complemented with NMES, TENS, ultrasound, hydrotherapy, and gait reeducation, in addition to the use of therapeutic education to improve the quality of life and the perception of pain in these patients [ 12 , 13 , 14 ]. Moreover, chronic pain appears in 35–50% of people with hemophilia, with 40% of these patients indicating that health professionals do not treat their pain well, requiring a better approach from a biopsychosocial sphere [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation